Comparison of Local and Taiwanese Managerial Leadership Styles as Perceived by the Malaysian Workforce of a Taiwanese Company in Malaysia: A Case Study - Wang, Chun Tao (2000)
The globalisation of business is a must for many multinational companies, including Taiwanese enterprises, to stay and prosper on the competitive edge of international business. Taiwanese Foreign Direct Investment (FDI) which began in 1986 has had special interest in the region of South East Asia, especially in Malaysia. Today, there is a need to take a closer look at the managerial leadership practices in Taiwanese enterprises within the Malaysian context so as to evaluate the current status and to provide a basis for future development and improvement. A survey Multifactor Leadership Questionnaire (MLQ) was randomly distributed to qualified respondents in a Taiwanese Electronics company. And 203 valid respondents provided relevant data for comparisons between Taiwanese and local superiors, which included leadership styles, leadership performance and the associated personal attributes. Confirmative factor analysis was used in accordance with the two-factor model and five-factor model of leadership style introduced by Bass (1985). Reliability tests showed that the constructs were valid and existed in this study. Leadership styles were compared between Taiwanese and local superiors by using paired T-test. Stepwise multiple-regression was applied to find out the leadership styles most associated with leadership performance. One way ANOVA and independent T-test were used to distinguish the personal attributes, which had perceived effect on the leadership styles. The results of this study showed that there were significantly different and yet similar leadership styles used by Taiwanese and local superiors. No extra-ordinary leadership styles were perceived among Charisma, Individual Consideration, Intellectual Stimulation, Contingent Reward and Management-by-Exception. Charisma was found to be most associated with leadership performance, which was the leadership effectiveness of superiors and the satisfaction of subordinates towards leadership. Previous working exposure to foreign leadership was a crucial factor in affecting subordinates' perception of leadership.